Effects of chickpea husk on the baking properties of chapattis - Inam, AKMS; Haque, MA; Shams-Ud-Din, M; Easdani, M (Journal of the Bangladesh Agricultural University, 2011)
Chickpea husks were extracted by non-alkaline aqueous extraction process and then ground in flour mill. The unextracted husks were also ground in flour mill. The analysis of chickpea husk showed that extracted husk was lower in moisture, protein, ash and fat but higher in carbohydrate and crude fiber contents compared to unextracted husk. Chapattis were prepared incorporating different levels of extracted and unextracted chickpea husk and evaluated for various quality parameters as weight, width, thickness, spread ratio, and moisture content. The chapatti containing extracted husk had higher moisture, carbohydrate and crude fiber content but lower in protein and ash content than that of chapatti containing unextracted husk. Chapattis were also prepared incorporating various levels of salt, baking powder and water. The quality of chapattis was evaluated. Chapatti prepared from 5% extracted husk required 2.0% salt, 1.5% baking powder and 62% water for producing reasonably acceptable quality while chapatti from 5% unextracted husk required 1.5% salt, 1.5% baking powder and 60% water for achieving better quality. Chapattis were prepared with 5% extracted husk required higher salt and water than that of 5% unextracted husk. Chapattis were evaluated organoleptically by a taste testing panel. The overall acceptability of chapattis without husk was followed by chapattis incorporated with 5% extracted husk. Keywords: Chickpea; Extracted husk; Unextracted husk; Baking; Chapatti DOI: 10.3329/jbau.v8i2.7941 J. Bangladesh Agril. Univ. 8(2): 297-304, 2010